ANALYSIS OF PERSONAL BRANDING STRATEGIES THROUGH DIGITAL STORY TELLING ON TIKTOK @ONEBITEBIGBITE ACCOUNTS - Rahmawati, Devi Irda; Febriana, Poppy (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the formation of personal branding through digital storytelling on the TikTok account @onebitebigbite, using McNally and Speak’s (2012) Personal Branding Theory to examine how creators establish a unique, relevant, and consistent self-image on social media. Method: Employing a qualitative approach with content analysis, data were collected from 50 TikTok videos uploaded between June and December 2024, with further analysis focused on the 10 videos receiving the highest engagement in the form of likes. Results: The findings reveal that @onebitebigbite successfully constructs personal branding by integrating distinctive visual styles (e.g., flashy lipsticks, glamorous outfits, dramatic expressions), relevant content themes (e.g., viral food trends, popular restaurants, extreme food portions), and consistent storytelling patterns, including strategic use of Call-to-Action features. This combination creates an authentic and recognizable brand identity, effectively enhancing audience engagement. Novelty: The study contributes to the refinement of personal branding theory in the context of digital media, highlighting the role of TikTok as a powerful platform for narrative-driven branding while offering practical insights for individuals and organizations seeking to leverage digital storytelling in branding strategies.